2016
DOI: 10.1177/0018726715611236
|View full text |Cite
|
Sign up to set email alerts
|

When saying sorry may not help: Transgressor power moderates the effect of an apology on forgiveness in the workplace

Abstract: When saying sorry may not help AbstractAn apology, as an expression of remorse, can be an effective response from a transgressor to obtain forgiveness from a victim. Yet, to be effective, the victim should not construe the transgressor's actions in a cynical way. Because low-power people tend to interpret the actions of high-power people in a cynical way, we argue that an apology (vs. no apology)from high-power transgressors should be relatively ineffective in increasing forgiveness from low-power victims. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 88 publications
(215 reference statements)
1
38
0
Order By: Relevance
“…Future research and theoretical models of reconciliation are needed to incorporate other transgressor‐specific antecedents. For example, it may be fruitful to consider the role of transgressor dispositional factors (Howell, Dopko, Turowski, & Buro, ), transgressor power (Zheng, van Dijke, Leunissen, Giurge, & De Cremer, ), or transgressor regret (Exline et al, ) when theorizing about the role of apology in the reconciliation process. Ultimately, to understand dyadic reconciliation, more research and theorizing about the transgressor perspective is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Future research and theoretical models of reconciliation are needed to incorporate other transgressor‐specific antecedents. For example, it may be fruitful to consider the role of transgressor dispositional factors (Howell, Dopko, Turowski, & Buro, ), transgressor power (Zheng, van Dijke, Leunissen, Giurge, & De Cremer, ), or transgressor regret (Exline et al, ) when theorizing about the role of apology in the reconciliation process. Ultimately, to understand dyadic reconciliation, more research and theorizing about the transgressor perspective is needed.…”
Section: Discussionmentioning
confidence: 99%
“…We focused our studies on one specific transgression-lateness to a workplace meeting-yet perhaps more severe or personally significant transgressions could lead to a different pattern of results. Many studies in this research area use a critical incident technique to prompt participants to think of the last time someone did something that offended them at work and then to write the explanation offered by the transgressor (e.g., Aquino, Tripp, & Bies, 2006;Bies & Shapiro, 1987;Tata, 2002;Zheng, van Dijke, Leunissen, Giurge, & De Cremer, 2016). Much attention has been focused on the explanation but fairly little work has explored the properties of the event that is being explained.…”
Section: Discussionmentioning
confidence: 99%
“…All these features may have an impact on the outcomes of our observed communication behavior, being either positive or negative. For example, it is previously argued that the tone of the response strategy determines whether something is considered sincere or not (Oostinga et al, 2018-a), and in turn research shows that sincerity determines whether responses lead to forgiveness or not (Zheng et al, 2016). Follow-up research may therefore take non-verbal behavior into account and find out how our findings translate to other interaction media.…”
Section: Discussionmentioning
confidence: 58%
“…For example, Coombs (1999) found that organizations who showed compassion after a crisis improved on their organizational reputation. Similarly, research on interpersonal relationships by Zheng et al (2016) demonstrates that after a transgression showing remorse can be an effective response to obtain forgiveness. Although these three categories of research each provide a deeper understanding of error making and management, the studies assess the different stages of error management in isolation.…”
Section: Error Management and Organizationsmentioning
confidence: 98%
See 1 more Smart Citation